Education Before Kidney Transplantation: What Do Patients Need to Know?. (March 2017) - Rosaasen, Nicola; Mainra, Rahul; Shoker, Ahmed; Wilson, Jay; Blackburn, David; Mansell, Holly
Context: Poor knowledge about immunosuppressive (IS) medications remains a major problem for patients in the posttransplant setting. Therefore, more effective educational strategies in the pretransplant setting are being considered as a possible method to improve knowledge and readiness for the challenges of posttransplant care. However, the most effective/relevant content of a pretransplant educational program is yet to be determined. Objective: To identify pretransplant education topics from the posttransplant patient perspective. Design: A focus group meeting was conducted among 7 high-functioning, stable adult kidney transplant recipients recruited from the Saskatchewan Transplant Program. Demographic information including age, gender, occupation, background/ethnicity, and time since transplant were recorded. A moderator, assistant moderator, and research assistant facilitated the 90-minute focus group meeting using a predetermined semistructured interview guide. The session was audio recorded and transcribed verbatim. Nvivo software was used to code the data and identify emerging themes exploring views of participants relating to the educational information required for pretransplant patients. Results: Patients were satisfied with the education they had received. Ideas were classified into the following major themes—patient satisfaction, transplant waitlist, surgery, medications, posttransplant complications, lifestyle and monitoring, knowledge acquisition, illusion of control, and life changes posttransplant. Knowledge gaps were identified in all areas of the transplantation process and were not exclusive to IS medications. Conclusion: Misconceptions regarding transplantation were identified by a group of high-functioning, stable adult recipients who were satisfied with their clinical care. Future educational strategies should aim to address the entire transplantation process and not be limited to medications.